The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/pam.10097
|View full text |Cite
|
Sign up to set email alerts
|

Welfare reforms, family resources, and child maltreatment

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 18 publications
1
70
0
Order By: Relevance
“…1 Two exceptions are Paxson and Waldfogel (2003) who examine child abuse and neglect and Meyer and Sullivan (2001) who examine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…1 Two exceptions are Paxson and Waldfogel (2003) who examine child abuse and neglect and Meyer and Sullivan (2001) who examine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have compared CPS involvement between pre-and post-welfare reform periods and across different welfare programs (Fein & Lee, 2003;Geen, et al, 2001;Goerge & Lee, 2000;Paxson & Waldfogel, 2003;Wells, Guo, Shafran, & Pearlmutter, 2003). It has been reported that CPS caseloads significantly increased after welfare reform and that foster care entry rates among children from welfare families rose in the first year of full implementation of a state's welfare reform program (Goerge & Lee, 2000).…”
Section: Welfare Work and Involvement With Cps: Current Empirical Knmentioning
confidence: 99%
“…One study showed that the rate of reported neglect was significantly higher among a group that faced strict work requirements and harsher penalty rules than among a group enrolled in a traditional welfare program (Fein & Lee, 2003). State-level analyses reported that the level of substantiated child maltreatment and the number of children in out-of-home care were higher in states with strict lifetime welfare limits and harsher penalty rules than in states with less strict rules (Paxson & Waldfogel, 2003). These studies suggest that welfare reform rules, especially work requirements and strict penalties, may increase welfare recipients' risk of being involved with CPS.…”
Section: Welfare Work and Involvement With Cps: Current Empirical Knmentioning
confidence: 99%
“…9 Several studies have reported associations between economic factors and maltreatment rates at the neighborhood and community levels. [12][13][14][15] Recently, a retrospective study of children admitted to 38 hospitals between 2000 and 2009 showed that rates of admissions for physical abuse and high-risk traumatic brain injury were significantly related to increases in local mortgage foreclosure and delinquency rates in the associated metropolitan areas. 16 Although there is considerable evidence that income inequality has a negative impact on health and wellbeing for both adults and children, and that poverty is associated with rates of child maltreatment, no study has examined the association of income inequality with child maltreatment.…”
mentioning
confidence: 99%